LOC101928834, a novel lncRNA in Wnt/β-catenin signaling pathway, promotes cell proliferation and predicts poor clinical outcome in myelodysplastic syndromes. Issue 11 (15th June 2020) - Li, Nianyi; Ma, Yan; Wang, Wei; Yin, C. Cameron; Wu, Wanling; Sun, Ruichen; Zhao, Guangjie; Li, Shuang; Wang, Xiaoqin
Abstract: Long non-coding RNAs (lncRNAs) play important roles in hematological malignancies. We have previously identified several differentially expressed lncRNAs in myelodysplastic syndromes (MDS) by microarray analysis. In the present study, we explored the regulatory circuitry, potential functions, clinical and prognostic relevance of these lncRNAs in MDS by developing a lncRNA regulation network. We identified a novel lncRNA, LOC101928834, which was significantly up-regulated in the bone marrow of patients with MDS and acute myeloid leukemia (AML). We further evaluated the clinical relevance of LOC101928834 in 89 MDS and 110 AML patients and found that higher level of LOC101928834 expression was associated with higher white blood cell count, higher blast percentage, the subtype of refractory cytopenia with excess blasts (RAEB) and shorter overall survival in MDS patients. Receiver operating characteristic (ROC) curve analysis showed that LOC101928834 expression could discriminate MDS-RAEB patients from control with an area under the receiver-operating curve (AUC) of 0.9048. Moreover, functional analysis showed that LOC101928834 promoted cell proliferation and cell cycle progression, and activated Wnt/β-catenin signaling pathway in vitro . In conclusion, LOC101928834 expression is correlated with clinical and biological features of MDS and may serve as a novel diagnostic and prognostic biomarker.